Persiapan Guru Dalam Melaksanakan Sistem Pembelajaran Merdeka Belajar Pada Tingkat Sekolah Dasar - Cindy Sinomi; Adisel Adisel; Fatrima Santri Syafri (GHAITSA : Islamic Education Journal, 2021)
This research was carried out with the aim of knowing Teacher Preparation in Implementing an Independent Learning System at SD N 01 Muara Pinang, Muara Pinang District, Empat Lawang Regency, South Sumatra Province. The learning system "Freedom of Learning" is a new policy which of course has obstacles and obstacles to implement. Especially for teachers who as an integral part in education and an important component in learning must have a series of problems that should be resolved. This type of research uses qualitative research using data collection techniques of observation, interviews and documentation. The subject of the study was the teacher of SD N 01 Muara Pinang, Muara Pinang District, Empat Lawang Regency, South Sematera Province. This study uses a qualitative descriptive data analysis interactive model of Milles and Michael Huberman. At SD N 01 Muara Pinang, Muara Pinang District, Empat Lawang Regency, South Sematera Province, the readiness of the independent learning system to learn starts from the readiness of the teachers first, SD N 01 Muara Pinang has held training for teachers, especially teachers who are still clueless in order to provide understanding and skills in utilizing online features as learning media. Factors that become obstacles for teachers in implementing an independent learning learning system are as follows: The quality of the human resources of the teachers is not adequate, the facilities and learning resources are minimal or the infrastructure is inadequate and the teachers are clueless, are comfortable with the old standards and have no experience in free learning